Plant germplasm collecting missions carried out from Mar 1987 to January 1989 in six African countries - Padulosi, S. (1990)
Collecting missions under the auspices of the IITA to Zimbabwe, Tanzania, Chad, Swaziland, Lesotho and Somalia covered over 24 000 km and collected 2023 accessions of cultivated crops and wild material. Details are given for each of the 6 missions, with information on routes taken, regions visited and accessions collected. The main crops sampled included: cowpeas (Vigna unguiculata), V. subterranea, wild Vigna species, maize and sorghum in Zimbabwe; cowpeas, wild Vigna species, Phaseolus vulgaris, rice and maize in Tanzania; cowpeas, V. subterranea, maize, sorghum and pearl millet (Pennisetum americanum) [P. glaucum] in Chad; wild and cultivated cowpeas and maize in Swaziland; cowpeas, P. vulgaris and maize in Lesotho; and cowpeas and maize in Somalia.